Immunogenetic diversity of MHC class II B-Lβ genes in Brazilian Caipiras (free-range) chickens laying blue eggs - Costamilan, Carlos André da Veiga Lima Rosa; Paludo, Ediane; Herkenhoff, Marcos Edgar; Pértille, Fábio; de Souza, André Luigi Soares; Mendes, Carolina Rosai; Dilarri, Guilherme (Frontiers in Immunology, 2025)
IntroductionBrazilian Caipira chickens that lay blue eggs are known to possess unique genetic traits. This study investigates the immunogenetic diversity of MHC class II B-Lβ genes (B-LβI and B-LβII) in this population, aiming to assess their potential value in selective breeding programs focused on disease resistance.Material and methodsA total of 100 chickens were analyzed using targeted sequencing of the B-LβI and B-LβII genes. The resulting nucleotide sequences were evaluated for polymorphism and compared with known alleles described in previous studies.ResultsFifteen unique nucleotide sequences were identified, of which five had not been previously reported in the scientific literature. The new alleles exhibited significant polymorphism, confirming high genetic diversity within the population. DiscussionThe genetic variability observed supports earlier findings regarding the diversity of MHC genes in local chicken breeds. These novel alleles may confer advantages in immune responsiveness, reinforcing the importance of preserving local breeds as reservoirs of functional genetic diversity. ConclusionBrazilian Caipira chickens laying blue eggs display remarkable immunogenetic diversity in MHC class II B-L β genes. This variation includes novel alleles with potential application in future breeding programs. Conservation and utilization of this genetic resource can contribute to the development of healthier and more disease-resistant commercial chicken lines.